2019
DOI: 10.1007/s13213-019-01468-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of thermotolerant yeasts for the production of second-generation bioethanol

Abstract: The purpose of this study was to isolate, identify, and characterize the thermotolerant yeasts for use in high-temperature ethanol fermentation. Thermotolerant yeasts were isolated and screened from soil samples collected from the Mekong Delta, Vietnam, using the enrichment method. Classification and identification of the selected thermotolerant yeasts were performed using matrixassisted laser desorption ionization/time-of-fight mass spectrometry (MALDI-TOF/MS) and nucleotide sequencing of the D1/D2 domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
5
26
0
1
Order By: Relevance
“…In the current study, some technological and in vitro probiotic properties of the selected strain were investigated according to the suggestion of FAO/WHO (14,25). As shown in Figure 2A, the isolated yeast strains have a strong ability to tolerate high temperatures and S. boulardii is viable at 45 • C, which agrees with the previous reports (35). Bile resistance is an important criterion in the selection of culture as a dietary adjunct because it could allow the growth of the ingested probiotic microorganism in the intestinal tract (6,7).…”
Section: In-vivo Antidiarrheal Activities For Safety Evaluationsupporting
confidence: 84%
See 2 more Smart Citations
“…In the current study, some technological and in vitro probiotic properties of the selected strain were investigated according to the suggestion of FAO/WHO (14,25). As shown in Figure 2A, the isolated yeast strains have a strong ability to tolerate high temperatures and S. boulardii is viable at 45 • C, which agrees with the previous reports (35). Bile resistance is an important criterion in the selection of culture as a dietary adjunct because it could allow the growth of the ingested probiotic microorganism in the intestinal tract (6,7).…”
Section: In-vivo Antidiarrheal Activities For Safety Evaluationsupporting
confidence: 84%
“…To determine the thermal stability of the yeast strain, SDB (Sabouraud dextrose broth) medium (Difco, Thermo Fisher Scientific) was prepared and transferred to tubes in 5 ml. An inoculum of yeast strain was prepared in SDB medium by overnight incubation and 1% (v/v) fresh culture was added to each tube and incubated for 24, 48, and 72 h at 25, 30, 35, 37, 40, 45, and 50 • C. After incubation, the survival rate of the isolate was measured by taking absorbance at 660 nm by a spectrophotometer (Thermo Multiskan EX) (19,35).…”
Section: Thermal Stability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies were addressed to the characterization of yeasts by identifying thermotolerant strains belonging to P. kudriavzevii and S. cerevisiae from fermented cocoa beans [ 28 , 33 ], and in industrial processes to improve the production of ethanol from sugar cane [ 46 , 47 , 48 ]. The thermotolerance of P. manshurica and C. parapsilosis isolated from fermented cocoa beans has never been reported before but a previous study found this characteristic in strains from soil samples collected from the Mekong Delta, in Vietnam [ 49 ], and from sugar cane from Brazil [ 48 ]. In addition, the thermotolerance of C. parapsilosis isolated from soil has been previously documented by El-Gamal et al, [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The DNA was sequenced using NL1 (5′-GCATATCAATAAGCGGAGGAAAAG-3′) and NL4 (5′-GGTCCGTGTTTCAAGACGG-3′) as PCR primers for amplification of D1/D2 region of LSU rDNA [ 24 ]. PCR amplification was performed in 20 μL reaction, containing 10 μL of GoTaq® Green Master Mix (Promega), 10 pmol of each primer, and 2 μL of 1–20 ng/μL extracted DNA, on GeneAmp® PCR System 9700 (Applied Biosystems) or iCycler (BioLad).…”
Section: Methodsmentioning
confidence: 99%